Inelastic displacement demand of bridge columns considering shear flexure interaction. - Zhang, Jian (Earthquake engineering & structural dynamics.)
Reinforced concrete bridge columns exhibit complex hysteretic behavior owing to combined action of shear, bending moment, and axial force under multi-directional seismic shakings. The inelastic displacement of columns can be increased by shear?flexure interaction (SFI). This paper develops a simple yet reliable demand model for estimating the inelastic displacement and ductility based on the nonlinear time history analyses of 24 full-size columns subject to a suite of near-fault ground motions. A coupled hysteretic model is used to simulate the shear-flexure interactive (SFI) behavior of columns and the accumulated material damage during loading reversals, including pinching, strength deterioration, and stiffness softening. Guided by rigorous dimensional analysis, the inelastic displacement responses of bridge columns are presented in dimensionless form showing remarkable order. A dimensionless nonlinearity index is derived taking into account of the column strength, ground motion amplitude, and softening or hardening post-yield behavior. Strong correlation is revealed between the normalized inelastic displacement and the dimensionless structure-to-pulse frequency, the dimensionless nonlinearity index as well as the aspect ratio. Two regressive equations for displacement and ductility demands are proposed and validated against the simulation results. The SFI effects are discussed and included explicitly through the aspect ratio in the proposed model. This study offers a new way to realistically predict the inelastic displacement of columns directly from structural and ground motion characteristics.